2016
DOI: 10.1111/ijlh.12466
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical comparison of different immunoassay systems for the detection of antiphospholipid antibodies

Abstract: By guidelines, all laboratories are strongly advised to validate/verify the manufacturer's cutoff values. We recommend establishing low-positive, medium-/high-positive, and high-positive CliA IgG aCL and a-β2GpI ranges in order to help clinicians in the diagnosis and treatment of APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Titers do correlate between systems, although the numerical values vary between test platforms 27,37 . Accordingly, it is nearly impossible to recommend a numeric value (it is >40 GPL/MPL 2 ) as general criterion for positivity.…”
Section: Anticardiolipin and Antibeta2‐glycoprotein I Antibodiesmentioning
confidence: 99%
“…Titers do correlate between systems, although the numerical values vary between test platforms 27,37 . Accordingly, it is nearly impossible to recommend a numeric value (it is >40 GPL/MPL 2 ) as general criterion for positivity.…”
Section: Anticardiolipin and Antibeta2‐glycoprotein I Antibodiesmentioning
confidence: 99%
“…This is evident by the different cut-off values of different brands of kits, and the wide range of results reported by labs during proficiency testing surveys [2,3,4,5]. Differences exist not only between various traditional, ELISA-based tests, but also between traditional tests and new technologies, such as chemiluminescent immunoassays (CIA) and addressable laser bead immunoassays (ALBIA) [6,7,8]. The analytical performance characteristics of these tests are often different from that of traditional technologies.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Mostly aCL and aβ2GPI antibodies are measured by ELISA, although chemiluminescence (CLIA) and fluorescence enzyme immunoassays (FEIA) have recently been introduced to the market. 16,17,[27][28][29][30][31][32][33] In most of the cases, fair to moderate agreement was found among different assays. 16,17,29,[31][32][33] de Moerloose et al 28 observed far higher agreement between three well-established commercial assays.…”
Section: Anticardiolipin and Anti-β2 Glycoprotein-i Antibodiesmentioning
confidence: 88%
“…Utilizing an automated system can improve reproducibility and reduce interlaboratory variation. [15][16][17][27][28][29][30][31][32][33] Willis et al 17 also analyzed that when the assays were calibrated using the recently developed reference IgG materials, the correlations for aβ2GPI antibodies were more improved.…”
Section: Anticardiolipin and Anti-β2 Glycoprotein-i Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation